AB0207 Specificity and Sensitivity Testing of New Systemic Scleroderma Criteria in the Russian Patient Population. (9th June 2015) - Ovsyannikova, O.B.; Koneva, O.; Ananyeva, L.; Alekperov, R.; Alexandrova, E.; Desinova, O.; Starovoitova, M.
Abstract : Background: Systemic sclerosis (SSc) is a heterogeneous disease, the clinical manifestations and the prognosis which depending on variable involvement of internal organs and having skin thickening. The new EULAR/ACR classification criteria for SSc have not been validated yet. That's why to assess specificity, sensitivity of new criteria is very important for practice. Objectives: A 115 patients have been recruited in "Nasonova Research Institute of Rheumatology". Diagnosis of SSc was established by experts in 85 pts and 30 pts had other rheumatic diseases (control group). Average age of the SSc pts was 51±12 years, with male/female (4/81), diffused and limited SSc ratio 1:1.9 (29 and 56), and disease duration from the first non-Reynaud's syndrome mediana 6 [4;13] years. A control group include 11 pts with systemic lupus erythematosus, 8 - rheumatoid arthritis, 2 – osteoarthritis, 1- polymyalgia rheumatica, 4 – ankylosing spondylitis, 2- polydermatomyositis, 1 – Bechet's disease, 1 – diffuse glomerulonephritis. Average age of the pts in control group was 45±13 years, with m/f (4/26). All pts underwent physical examination, wide-field videocapillaroscopy, lung X-ray radiography or computed tomography, echocardiographic measurements of the pulmonary artery systolic pressure, and assay for SSc-specific antibodies (a-Scl-70, ACA, RNAP-III).Specificity was determined using the following formula: SP = D/(B+D) × 100% ( SP is specificity; D is a number of pts don't qualify as SSc or stands for absence of signs; B is a number of pts qualify as SSc or stands for presence of signs ). Methods: Based on the new criteria SSc was not diagnosed in control group. Specificity for each sign was: skin thickening of the fingers of bath hands extending proximal to the metcarpophalangeal joints was observed in 0/100% skin thickening of the fingers in 0/100% of cases, fingertip lesions in 0/100% of the patients, telangiectasia in0/100%, abnormal nailfold capillaries in 10/67%, pulmonary arterial hypertension (PAH) or interstitial lung disease (ILD) 5/83% (ILD in 5/17% of the patients), Reynaud's phenomenon in 17/43%, SSc-related autoantibodies in 2/93% of the pts (a-SCL-70 in 1/97%, RNAP1/97% of the patients). Specificity for ACR/EULAR 2013and for 1980 ACR criteria SSc was 100%.Based on 1980ACRcriteria SSc was diagnosed in 48 (56%). Based on ACR/EULAR 2013 criteria SSc was diagnosed in 70 (82%) without RNAP detection. When RNAP has been assessed, 8% SSc pts were positive for RNAP and SSc sensitivity improved to 85% (72 pts).Sensitivity for SSc-related autoantibodies was 66% (56 pts): a-Scl-70 in 36/44%, ACA in 9/11%, ACA plus a-Scl-70 in 2/2%, RNAP 3/3.5%, RNAP plus a-Scl-70 in 3/3.5%, RNAP plus ACA 2/2%of the patients. Conclusions: The new ACR/EULAR classification criteria for SSc in the Russian patient population have 85% sensitivity and 100% of specificity. Raynaud's phenomenon and abnormal nailfold capillaries pictures have the lowest specificity. Measurement of RNAP in SSc pts benefits sensitivity of novel criteria and is useful for the diagnosis. Disclosure of Interest: None declared